PENDAFTARAN TANAH MILIK ADAT MENJADI HAK MILIK PADA KANTOR PERTANAHAN KABUPATEN ACEH TAMIANG - BAMBANG SUWITO S. (PREMISE LAW JURNAL, 2014)
ABSTRACT   All people want to get a land registration service with easy procedure and can be understood by the holders of the rights to adat land who want to change their land document into the property right certificate. One of the important functions of land registration is to ensure the existence of legal certainty related to various rights to land and legal protection for the rights holders. Therefore, the questions to be answered in this study were how community legal awareness was performed in registering the change of the status of adat land into private property at Aceh Tamiang District Land Office, what terms and procedures were applied in registering the change of the status of adat land into private property at Aceh Tamiang District Land Office, and what constraints were faced by Aceh Tamiang District Land Office in the registration of the change of the status of adat land into private property. It is suggested that with the orderly and up to date land administration, the community members and the government can easily get the data needed to do a legal action or to make a planning for the plots of lands quickly and acuurately  to avoid “brokering of land” that eventually can result in high cost economy. The government should keep legalizing the status of the lands belong to the underprivileged communities. Keywords: Land Registration, Adat Land,  Certificateof ProprietaryRights